Protective Activity of Streptococcus pneumoniae Spr1875 Protein Fragments Identified Using a Phage Displayed Genomic Library - Cardaci, Angela (Public Library of Science, 2012)
There is considerable interest in pneumococcal protein antigens capable of inducing serotype-independent immunoprotection and of improving, thereby, existing vaccines. We report here on the immunogenic properties of a novel surface antigen encoded by ORF spr1875 in the R6 strain genome. An antigenic fragment encoded by spr1875, designated R4, was identified using a Streptococcus pneumoniae phage displayed genomic library after selection with a human convalescent serum. Immunofluorescence analysis with anti-R4 antisera showed that Spr1875 was expressed on the surface of strains belonging to different serotypes. Moreover, the gene was present with little sequence variability in 27 different pneumococcal strains isolated worldwide. A mutant lacking Spr1875 was considerably less virulent than the wild type D39 strain in an intravenous mouse model of infection. Moreover, immunization with the R4 recombinant fragment, but not with the whole Spr1875 protein, induced significant protection against sepsis in mice. Lack of protection after immunization with the whole protein was related to the presence of immunodominant, non-protective epitopes located outside of the R4 fragment. In conclusion, our data indicate that Spr1875 has a role in pneumococcal virulence and is immunogenic. As the R4 fragment conferred immunoprotection from experimental sepsis, selected antigenic fragments of Spr1875 may be useful for the development of a pneumococcal protein-based vaccine.